Edible Bird’s Nest as Potential Food with Anti-Viral and Anti-Inflammatory Properties Against Covid-19: an in Silico Study - Siti Gusti Ningrum; Rochiman Sasmita; Viol Dhea Kharisma (IPB University, 2023)
The Chinese believe consuming edible bird’s nests (EBN) can increase immunity to various diseases, including Covid-19. This study attempts to identify SARS COV-2-specific anti-viral and anti-inflammatory agents of EBN. We gathered samples from PubChem and Protein Data Bank (PDB). Afterwards, drug likeness was examined using the Lipinski model from the SCFBIO online service. The PASS web server analyzed the bioactive likelihood of chemicals found in EBN. Using PyRx 0.8 software with the blind docking technique. The PoseView web server and PyMol v2.4.1 software were utilized to ascertain molecular interactions. The in silico results show the potential of EBN as food therapy for Covid-19 sufferers, which is indicated by the presence of bioactive compounds from edible bird’s nest consisting of 9-O-acetylated GD3, glycopeptide, N-acetyl neuraminic acid, N-glycolyl-neuraminic acid, sialic acid, and tetra acetyl-thymol-beta-D-glucoside. These bio compounds are predicted to work as anti-viral and anti-inflammatory candidates against SARS-COV-2.